Fra undtagelsesregel til undtagelsestilstand: Politiske og kirkelige hensyn til modstandere af kvindelige præster 1947-2007 - Hansen, Ole Hyldegaard (Kirkehistoriske Samlinger, 2013)
Udtrykket “en håndsrækning” anvendes normalt som en understøttende, anerkendende og inkluderende gestus mellem to parter. Den man rækker hånd, viser man sin sympati. Håndsrækning eller håndtryk indgår også i Den Danske Folkekirkes præstevielsesritual, hvor biskop, assisterende præster og øvrige tilstedeværende præster forventes at give den nye kollega hånden umiddelbart efter ordinationen. I 60 år – fra 1947 til 2007 – var det imidlertid på grund af politiske og kirkelige hensyn muligt for mandlige præster i folkekirken at blive fritaget for denne anerkendelse af deres kvindelige kolleger, hvis det inderligt stred imod deres samvittighed og teologiske embedssyn. Hvordan dette lod sig praktisere, er genstand for denne kirkehistoriske undersøgelse. Summary According to the 1912 Rite of Ordination to the Priesthood, ordinands in the Danish Folkchurch were required to shake the hand of all clergy who were present. This was changed in the 1992 Rite, which is currently valid, so that ordinands can, as a minimum, shake the hand of bishops and those pastors who are present as readers. The parliamentary act of 1947 giving women the right to be ordained as pastors has been seen as a challenge to this rite and to those bishops and clergy who for reasons of scripture and church unity do not recognise female pastors. In the case of the bishops a law was later passed enabling them to be exempt from pastoral supervision of churches and their female clergy. This law was applied by Bishops Plum and Fuglsang-Damgaard in 1948 and by Christian Baun in 1956 – after deep consideration – in the interests of church unity, the churches’ wishes, and respect for the collegium of bishops. Since 1968 no bishop has opposed the ordination of female pastors. While bishops ordain and supervise the clergy, it is normally the deans who perform pastoral inductions. However, in 1949 it was agreed that the bishops’ right to exemption should also be extended to the deans, an arrangement that lasted until 1980, when Dean Ørum Jorgensen, chair of the Home Mission Society, was refused an application for such an exemption. In connection with the induction of a female pastor in 1985 the Dean therefore resigned his chairman’s post. What remains is the pastors’ individual freedom of conscience. Bishops (Jacobsen, Geil and Nissen) in the Diocese of Viborg now take the practical step at ordinations of allowing male ordinands who are opposed to female pastors to refrain from the shaking of hands. Since in 2007 there is almost as many female as male pastors in the Danish Folkchurch; the established practise now was considered as problematic – and one which, after personal consideration and church reconnoitring, the current Bishop, Karsten Nissen, has chosen to abolish. He joins a number of other bishops who interpret the handshake as a recognition that the ordinands’ vows have been taken – while the gender aspect is toned down. This shift of emphasis has made the rite acceptable to the conservative wing of the church.